The updated evidence of pirfenidone treated silicosis based on network pharmacology, molecular docking and experimental validation - Chang, Sirong; Wen, Shengpeng; Zhang, Wenyue; Zhang, Huning; Guo, Yi; Wang, Qiushi; Hu, Xiaokun; Liu, Zhihong; Sun, Yue; Yang, Anning (Frontiers in Medicine, 2025)
ObjectiveSilicosis remains a debilitating occupational lung disease with limited therapeutic options, despite emerging evidence supporting pirfenidone’s (PFD) anti-fibrotic efficacy in clinical practice. However, the molecular circuitry governing PFD’s therapeutic actions in silicosis remains incompletely mapped, hindering mechanism-driven therapeutic optimization. To bridge this knowledge gap, we executed network pharmacology to replenish its molecular mechanisms and potential therapeutic targets.Materials and methodsWe replicated a silicosis C57BL6/J mouse model and evaluated inflammation and fibrosis using HE, Masson, and Sirius Red staining assays. The expression of fibrotic markers α-SMA and Fibronectin were determined by immunofluorescence assay. Network pharmacology and molecular docking were used to predict potential therapeutic mechanisms and targets. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) and immunofluorescence experiments were verified as the key predicted targets.ResultsPFD alleviated the level of inflammation and collagen deposition and fibrotic markers α-SMA and Fibronectin expression in silicosis lung. Network pharmacology analysis predicted three potential target proteins, including TNF, MMP9, and NF-κB1, as well as ten possible signaling pathways. Molecular docking showed a good binding activity between PFD and hub genes. qRT-PCR and immunofluorescence confirmed that PFD inhibited TNF, MMP9, and NF-κB activation. Additionally, we found increased expression of TLR2, a key upstream gene of NF-κB.ConclusionIn conclusion, we identified TNF, MMP9, NF-κB1 and TLR2, that contribute to the therapeutic effects of PFD in silicosis. Mechanistically, PFD appears to mitigate silicosis pathogenesis through suppression of epithelial TLR2/NF-κB pathway activation.